PROBLEMATIC AND APPROACH OF SOLUTIONS TO CONGO RIVER IRRATIONAL EXPLOITATION OF HALIEUTIC RESOURCES IN KINDU TOWN - Kabingwa Cyprien, Lundimu Kabingwa Cyprien (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
The Congo River halieutic resources non rationale exploitation in Kindu town caught my mind. The present descriptive scholarly paper uses the Accelerated Method of Research and Participatory Planning, a tool which involves inquired people to find solution to their specific problems, applying a semi-structured interview.